PEMETAAN DINAMIKA WILAYAH ENDEMIK PENYAKIT DEMAM BERDARAH DENGUE KOTA SALATIGA MENGGUNAKAN PENDEKATAN MULTIVARIAT LOCAL INDICATOR SPATIAL ASSOCIATION - Yulianto J.P., Sri; Hartati, Sri (Jurnal Informatika, 2012)
The objective of this study is to map the change dynamic of dengue endemic area in Salatiga, Central Java in 2001-2008. This study is carried out in three stages. The first one is the descriptive survey to find the secondary sociodemographic and epidemiologic data. The second stage is data analysis using spatial association, in this case is Global Moran’s dan Local Moran’s (LISA). The last stage is the interpretation of the result of analysis in form of Moran Scatterplot and LISA map. The result of the study shows that spatial pattern based on the dynamic distribution of Dengue occurrence could be identified using Global Moran’s method. From 2001 to 2008, it could be found that there are hotspots and outlier. The area with high frequency of hotspot is Sidorejo Lor, Mangunsari and Kutowinangun. Using Local Moran’s I method, the spatial pattern of the distribution of dengue could be visualized in form of LISA (Local Indicator Spatial Association) map. The map is categorized into HH, HL, LH dan LL. The ABJ value is not significant with the dengue happenings in each village. The area with high ABJ is not followed by the high value of dengue happening. Based on the choropleth, it could be described that the dengue happening is caused by the dense of the population. The result of this study could be used as a tool to control and identify the cause of dengue.